2022
DOI: 10.3171/2021.12.focus21629
|View full text |Cite
|
Sign up to set email alerts
|

Update on intrathecal management of cerebral vasospasm: a systematic review and meta-analysis

Abstract: OBJECTIVE Aneurysmal subarachnoid hemorrhage (aSAH) accounts for a relatively small portion of strokes but has the potential to cause permanent neurological deficits. Vasospasm with delayed ischemic neurological deficit is thought to be responsible for much of the morbidity associated with aSAH. This has illuminated some treatment options that have the potential to target specific components of the vasospasm cascade. Intrathecal management via lumbar drain (LD) or external ventricular drain (EVD) offers unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 69 publications
(63 reference statements)
0
11
0
1
Order By: Relevance
“…Comparisons of the effectiveness of enteral and intravenous DCI prophylaxis with nimodipine cannot yet be definitively evaluated [14]. Moreover, intrathecal therapies are described in connection with CVS and have been endorsed with the focus being placed on nimodipine in the form of slow-release microparticles in addition to the use of, e. g., magnesium [13,15,16]. However, a clear recommendation is lacking here as for endovascular spasm therapy (EST).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons of the effectiveness of enteral and intravenous DCI prophylaxis with nimodipine cannot yet be definitively evaluated [14]. Moreover, intrathecal therapies are described in connection with CVS and have been endorsed with the focus being placed on nimodipine in the form of slow-release microparticles in addition to the use of, e. g., magnesium [13,15,16]. However, a clear recommendation is lacking here as for endovascular spasm therapy (EST).…”
Section: Introductionmentioning
confidence: 99%
“…Ferner sind auch intrathekale Therapien im Zusammenhang mit ZVS beschrieben und befürwortet worden, wobei neben der Anwendung von z. B. Magnesium der Fokus auf wiederum Nimodipin in Form von sich langsam freisetzenden Mikropartikeln gelegt wird [13,15,16].…”
Section: Introductionunclassified
“…Although it has a short duration and a low clearance rate of bloody cerebrospinal fluid, it is the preferred method for relieving acute hydrocephalus ( 7 ). Ventricular and lumbar drainage can enhance cerebrospinal fluid circulation and facilitate the elimination of toxic substances in bloody cerebrospinal fluid ( 8 ). Previous studies have shown that acute hydrocephalus is caused by blockage of cerebrospinal fluid (CSF) outflow from the ventricular system, whereas chronic hydrocephalus is associated with arachnoid granulations and fibrosis of the leptomeninges caused by aSAH.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to remove the blood in the basal cisterns as the causative agent for vasospasm by surgery, cisternal, or external ventricular drainage showed mixed results . In retrospective studies, prophylactic lumbar drainage of cerebrospinal fluid was associated with favorable outcome . A plausible mechanism of action is increased removal of blood and its degradation products using gravity.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 , 10 In retrospective studies, prophylactic lumbar drainage of cerebrospinal fluid was associated with favorable outcome. 11 , 12 A plausible mechanism of action is increased removal of blood and its degradation products using gravity. However, the prospective Lumbar Drainage in Subarachnoid Haemorrhage (LUMAS) trial randomizing 210 patients was unable to confirm a benefit of lumbar drains.…”
Section: Introductionmentioning
confidence: 99%